The Implementation of Phonetic Transcription Strategy in Teaching Pronunciation to Students with Hearing Impairment (Scripta : English Department Journal, 2026)
This research explores the use of phonetic transcription as a method for teaching English pronunciation to Grade 9 students with hearing disabilities at a Sekolah Luar Biasa (SLB) in North Sumatra, Indonesia, along with the difficulties encountered by the classroom teacher during this implementation. Using a descriptive qualitative approach, data were gathered via classroom observation, a semi-structured interview, and documentation, then analyzed following Braun and Clarke's six-phase thematic analysis framework. The results indicate that the educator utilized phonetic transcription via three main practices: independent preparation with digital tools, structured repetition paired with visual aids like IPA charts and vocabulary images, and a multimodal feedback strategy that included hand signals and clear mouth and tongue demonstrations. Two primary challenges were identified: students' struggles with recognizing and producing IPA symbols, especially for phonemes involving invisible articulators like /r/, and the diversity of students' residual hearing capabilities, leading to inconsistent learning results within the same classroom. These results suggest that phonetic transcription can serve as a visually based pronunciation aid for learners with hearing impairments, yet it necessitates additional tactile approaches and focused professional training for SLB teachers to enhance its efficacy.